THE USAGE OF GAMING TECHNOLOGIES IN PRACTICAL ENGLISH CLASSES IN HIGHER EDUCATIONAL INSTITUTIONS - Волох, Світлана (Current Issues of Foreign Philology, 2021)
The article highlights the application of game technologies in English language teaching in higher education institutions, compares traditional teaching approaches and game technologies. The essence of the concept of gamification in the educational process is investigated, its advantages and disadvantages in comparison with traditional teaching methods are determined, examples of application of gamification in education are given. The aim of the article is to promote the development of new, progressive approaches to learning and expand their use in practical English classes in high school. The study used descriptive and comparative methods, as well as the classification procedure to analyze the phenomenon of gamification and determine its main features. At the present stage, traditional forms and methods of teaching are really becoming less effective among young people due to the fact that they have low motivation to learn and everyday life is oversaturated with the use of electronic gadgets. Therefore, one of the means to improve learning is the use of game technology or "gamification", Digital Game Based Learning (DGBL) – learning in which computer games are used. The main advantages of gamification are motivating students, involving them in active activities, introducing an element of competition, encouragement, making greater efforts to learn and concentrate, improving the atmosphere in the classroom. The use of gamification is possible without information technologies, but the use of computer games or online components will enrich educational games and benefit the training of specialists. The difficulties of introducing gamification into the educational process are determined by the complexity of preparation of educational tasks, the necessity of using the technical means, possible difficulties in the use of them in the classroom and computer literacy of teachers. In Ukraine, gamification is not widespread, however, taking into consideration a number of advantages over traditional approaches, it can be gradually introduced into the educational process in order to modernize the teaching of foreign languages in the higher educational institutions of Ukraine. Examples of the usage of gaming technology in education are online services and educational platforms. Duolingo is a service for self-study of a foreign language, which at the same time provides a service for its use in educational institutions. Edmodo and Kahoot are game-based learning platforms that can be used in foreign language classes. Gamification helps to teach effectively, motivates cooperation and interaction between participants, but it should be remembered that the use of game technology in institutions is not entertainment or a substitute for the teacher. Gamification of the educational process, according to the author, in some cases is more effective in teaching modern students comparing to traditional methods and successfully complements them. Taking into account the above, it is important to introduce moderate gamification in the educational process in Ukraine, considering all the advantages and difficulties of this phenomenon.